2016
DOI: 10.5993/ajhb.40.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms, Perceptions and Dual/Poly Tobacco Use among Texas Youth

Abstract: Objectives We assessed risk perceptions and social norms about tobacco use across adolescent non-users of tobacco, single-product users, and dual/poly-product users. Methods Use behaviors specific to e-cigarettes, cigarettes, hookah, cigars, and smokeless tobacco were assessed among 6th, 8th and 10th grade students (sample [n] = 3907 from a population of [N] = 461,069 students). Multivariate regression was used to examine differences in these factors across use categories, adjusted for demographic factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
0
35
0
1
Order By: Relevance
“…In contrast, 53% of adolescent multiple-product users reported e-cigarettes as not at all harmful to health, compared to 43% of single-product users in Texas. 17 In addition, 21% of poly-tobacco users reported that cigarettes are not at all harmful, compared to 6% of single-product users. 17 Our findings suggest that those with a high-risk perception of either or both products have a lower likelihood of using cigarettes and e-cigarettes and their own or concurrently.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, 53% of adolescent multiple-product users reported e-cigarettes as not at all harmful to health, compared to 43% of single-product users in Texas. 17 In addition, 21% of poly-tobacco users reported that cigarettes are not at all harmful, compared to 6% of single-product users. 17 Our findings suggest that those with a high-risk perception of either or both products have a lower likelihood of using cigarettes and e-cigarettes and their own or concurrently.…”
Section: )mentioning
confidence: 99%
“…Some of these studies have found that perceived risk was negatively associated with dual-use. 16,17 Cooper et al 16 found that college students' perceptions of cigarette and e-cigarette harm were lower among exclusive and dual-users than nonusers. A 2014-2015 study of Texas youth found that 53% of multiple-product users reported e-cigarettes as not at all harmful to health, compared to 43% of single-product users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumers have different reasons for using, and varied expectations regarding the perceived benefits and risks of e-cigarettes in general, by product type, and in comparison to conventional cigarettes (Ambrose et al, 2014; Brose et al, 2015; Chaffee et al, 2015; Cooper et al, 2016; Gorukanti et al, 2016; Roditis, Delucchi, et al, 2016). Therefore, researchers should not simply substitute “e-cigarette” or “vaping” into existing cigarette perception measures.…”
Section: Categories Of E-cigarette Perceptionsmentioning
confidence: 99%
“…Cross-sectional studies of youth find that favorable e-cigarette perceptions (e.g., they are “not addictive” or users “look cool”) are associated with youth e-cigarette use (Ambrose et al, 2014; Chaffee et al, 2015; Cooper et al, 2016; Gorukanti, Delucchi, Ling, Fisher-Travis, & Halpern-Felsher, 2016) and intentions (Chaffee et al, 2015). Among youth, favorable perceptions of e-cigarettes are particularly concerning because nicotine may affect adolescent brain development (Dwyer et al, 2009; England et al, 2015; U.S.…”
Section: Introductionmentioning
confidence: 99%